Medium‐term absorption kinetics and thermal stability analysis of hybrid fiber metal laminate and experimental investigations on its physical and tensile properties. Issue 8 (5th July 2021) - M, Saravana Kumar; M, Vasumathi; S, Rashia Begum; Pulikkalparambil, Harikrishnan; Siengchin, Suchart; Pruncu, Catalin I.
Abstract: Fiber metal laminates (FML) are promising material candidates in several applications such as aerospace, marine, and construction industries due to their high strength, impact resistance, corrosion resistance, and fatigue properties. However, these materials have a negative impact on the environment due to their higher carbon footprint. This problem could be overcome by hybridizing carbon material with natural biodegradable materials. It is assumed that the higher moisture absorption and lower thermal properties of such materials may affect the long‐term stability of the FML. Hence, an attempt is made in this work to evaluate their stability potential by investigating the influence of the addition of natural jute fiber in carbon reinforced aluminum laminate (CARALL) on FML and report their physical effect of stacking sequence on dynamic, mechanical, and thermal properties. In addition, the medium‐term absorption kinetics of jute fiber hybridized CARALL, that is, carbon‐jute reinforced aluminum laminate (CAJRALL) were performed. The results show that the tensile load bearing capacity of all the immersed laminates decreases at the end of 2 weeks of immersion. Further, CAJRALL was found to possess moderate thermal stability by yielding fewer thermal residues on burning. Finally, the outcome of dynamic mechanical analysis of the hybridized FML reveals that they are capable of storing relatively higher elastic and viscous energies under dynamic conditions with increased damping capability when compared to CARALL. From this study, it is worth to point out that hybridization of CARALL with jute fiber plays a pivotal role in improving environmental friendliness with a lower impact on the overall material properties. Abstract :